Exploring electric vehicles attributes and users’ satisfaction based on driving experience - Dinis, Lourenço Cabral (2021)
The acquisition of battery electric vehicles (BEVs) has been strongly promoted by the government for the last years due to the growing environment concerns towards the global warming due to the release of greenhouse gas emissions prevenient from the use of fossil fuels. However, BEV market share is still low, so it is important to understand the big picture. To determine the current conditions of BEV owners experience it is important to evaluate BEV users’ satisfaction. Based on driving experience and the theory of planned behaviour, it was established a framework containing the consumer´s evaluation about BEV attributes as well as their driving experience and satisfaction. Thus, empirically, this thesis examines into what extent the driving experience influences the consumer’s perception in what concerns the characteristics of these vehicles. On the other hand, it also tries to understand in what way it influences the previous BEV owners to repurchase these type of vehicles and recommend them to others, also based in their driving experience and satisfaction. This study collected and analysed the self-reported opinions of actual BEV owners (N=279) with different levels of driving experience. The results show that both driving experience and attitudes towards BEV attributes (except from attitudes towards charging infrastructures) positively affects the overall satisfaction of BEV users. Furthermore, those who are satisfied with BEVs have the intention to repurchase and recommend them to others. Nevertheless, the results also reveal that the evaluation of BEV attributes does not change with increasing driving experience. Considering that this study was based on actual experience of BEV owners, such findings could enhance the understanding of BEV driving status and, hence, allow better services for BEV users.